1990
DOI: 10.1002/j.1556-6676.1990.tb02519.x
|View full text |Cite
|
Sign up to set email alerts
|

The University Counseling Center: An Agenda for the 1990s

Abstract: Changes in higher education will hold special relevance for university counseling centers in the 1990s. Opportunities will exist for counseling center personnel to help institutions deal with some emerging problems. Research is reviewed that indicates that crisis management services, career development concerns, a changing student population, and issues related to retention all represent areas in which contemporary counseling centers could make significant contributions. Recommendations are made about how coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 25 publications
0
78
0
2
Order By: Relevance
“…Research has found that university students are subjected to high levels of stress (Bishop, 1990;Gall, Evans, & Bellerose, 2000), and perceive academic life as stressful and demanding (Hammer, Grigsby, & Woods, 1998). Over time, the types of psychological problems bringing students to counseling centers have changed significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that university students are subjected to high levels of stress (Bishop, 1990;Gall, Evans, & Bellerose, 2000), and perceive academic life as stressful and demanding (Hammer, Grigsby, & Woods, 1998). Over time, the types of psychological problems bringing students to counseling centers have changed significantly.…”
Section: Introductionmentioning
confidence: 99%
“…n the university setting, counselors are providing services for a more racially and ethnically diverse campus constituency (Bishop, 1990;Glauser & Ginter, 1995;Stone & Archer, 1990). Similarly, the counseling literature is placing greater emphasis on the role of race and ethnicity in psychosocial development, adjustment, and client needs (Comas-Diaz & Greene, 1994;Helms, 1994;Santiago-Rivera, 1995;Weinrach & Thomas, 1996).…”
mentioning
confidence: 98%
“…As has been noted elsewhere (Bishop, 1990), the role of a counseling center director is becoming more demanding and complex, and it is crucial for such individuals to have the requisite administrative skills and inclinations for the job. For most centers, it is no longer sufficient to have the director perceived as a senior psychologist who does a few administrative tasks on the side.…”
Section: Administrative Leadershipmentioning
confidence: 96%